Enhancing self-efficacy in 8th grade students through group guidance at MTS UINSU Medan - Luthfi, Sofyan; Sahputra, Dika (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study aimed to examine the efficacy of group guidance in enhancing the self-efficacy of 8th grade students at MTs Laboratorium UINSU Medan by comparing the self-efficacy exhibited by students in the experimental and control groups. The research methodology employed was quantitative, and utilized a quasi-experimental design. This investigation was conducted at the MTs Laboratorium UINSU Medan during the semester of the 2023/2024 academic year. The study population comprised all VIII grade students at the MTs Laboratorium UINSU Medan. The sampling technique utilized was purposive sampling, based on specific considerations and recommendations from the counseling teacher. Data were collected using a Likert scale questionnaire and analyzed using normality and homogeneity tests, followed by hypothesis testing (t-test) with the assistance of SPSS version 26. The findings indicated that the experimental group pre-test mean was 58.4, and the control group was 53.2, while the mean post-test scores for the experimental group were 91.5, compared to 78.2, respectively. The increase in student scores from pre-test to post-test in the experimental group was 33.1, whereas in the control group, it was 25. Data analysis yielded a Sig. (2-tailed) value of 0.000, respectively. With Sig.0.000 < 0.005, the hypothesis test results reject H0 and accept Ha. This demonstrates the significant effect of the implementation of group guidance on increasing student self-efficacy.